101 A report on the benefit and acceptability of a NEWS based acute illness management plan in a hospice inpatient unit. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Tinker, Andrew; Kane, Christopher; Russon, Lynne
Abstract : Background: Over recent years we have had increasing numbers of acute admissions, with potentially reversible conditions, as well as noticing increasing use of intravenous antibiotics, without any structured monitoring of progress. We have introduced an Acute Illness Management Plan (AIMP) including regular observations with triggers for medical review, based on the Royal College of Physicians National Early Warning Score (NEWS). This change was introduced alongside improving oxygen prescribing and administration, and an education programme, and is being followed with ongoing quality improvement work. It is important to ensure staff feel a change is worthwhile and important to ensure they are motivated to develop this further. We aimed to assess acceptability of an acute illness management plan in a hospice setting. Methods: We undertook a mixed survey with both quantitative and qualitative sections. This was analysed using a narrative approach. Results: All respondents feel the AIMP represents an improvement in the care offered to acutely ill patients in the hospice setting. The Majority (60%) felt the AIMP is acceptable in the hospice setting and (40%) felt it is sometimes acceptable. No staff felt it was inappropriate in a hospice setting. Additional comments include: Concerns about stopping treatment when a patient is felt to be clearly in the last days of life; Concerns about documenting individualised goals or triggers for medical review, to avoid frequent observations not leading to changes in treatment; A need for improved recording of urine output; A desire for more training in acute illness management. Conclusions: The AIMP acceptable in a hospice setting. Future work will include incorporating NEWS2 guidance, and an ongoing quality improvement programme to look at areas where it could be used more effectively. This will allow us to determine the efficacy of the AIMP along with ensuring staff feel empowered in the process of its introduction.